2009
DOI: 10.1177/000494410905300206
|View full text |Cite
|
Sign up to set email alerts
|

Junior Secondary Students' Perceptions of Influences on Their Engagement with Schooling

Abstract: Various explanations and solutions have been proposed over the last decade in relation to the implications of students' apparent lack of engagement with middle years schooling in Australia. In this article we report on responses to a questionnaire by 333 Year 8 students (aged about 13, the second year of high school) on perceptions of factors relating to their engagement with the academic curriculum. We found that while the majority of students reported a strong sense of the importance of, and opportunities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…A lot of research and work such as [61] and [62] on student participation in the classroom has been carried out, but there are still difficulties in keeping students involved in their activities. Reference [63] states that it is complex for students to develop levels of participation to achieve their maximum learning potential.…”
Section: B Gamification In Educationmentioning
confidence: 99%
“…A lot of research and work such as [61] and [62] on student participation in the classroom has been carried out, but there are still difficulties in keeping students involved in their activities. Reference [63] states that it is complex for students to develop levels of participation to achieve their maximum learning potential.…”
Section: B Gamification In Educationmentioning
confidence: 99%
“…Newmann [3] first discussed the importance of engagement in the educational process defining student engagement as the student's psychological investment in and effort directed toward learning, understanding, or mastering the knowledge, skills, or crafts that academic work is intended to promote. Additional studies investigated the relationship between school engagement and dropping out [4] [5], while other researchers identified the engagement in terms of autonomy [6] [7]. In a more recent study, Zepke et al [8] also suggested that engaged students usually succeed on their activities when they are intrinsically motivated and feel capable of working in an autonomous way.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Martino and Zan (2010) highlight how attitudes towards mathematics are related to perceived competence, and how changing the notion of success away from the production of correct and quick answers to the activation of meaningful thought processes can alter a person's emotional disposition to mathematics and their perceived competence. Likewise, Sullivan et al (2009) identify that a student's sense of what they can achieve can affect their engagement in that students who lack strategies to engage with a task or do not know how to improve their learning can become disengaged. Students need both the will and the skill to engage (Pintrich & de Groot, 1990).…”
Section: Evidence From Research: the Influence Of Affectmentioning
confidence: 99%